Associations of serum lithium, nickel, cobalt, and manganese with chronic kidney disease among Chinese older adults: Mediating role of lipid metabolism and moderating effect of lifestyle - Yan Wang; Qingping Liu; Wenyuan Zhu; Xiaoqing Ma; Tao Zhang; Mengqi Zou; Mengruo Wang; Lei Bao; Yaxian Pang; Tao Jing; Rong Zhang (Environmental Pollution, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Assessing the impact of the Lahaina Maui wildfire on chemical and microbiological quality of coastal beach water - Yangyang Zou; Min Ki Jeon; Xin Wang; Mandy-Tanita Brinkmann; Kexin Rong; Xiaolong Geng; Tao Yan (Environmental Monitoring and Assessment, 2026)

Electric field-induced gradient polyanionic hydrogel electrolytes with zinc-ion selective transport for stable zinc-ion batteries - Dan Rong; Shujun Zou; Yan Wu; Sijing He; Qinfeng Rong (Chemical Engineering Journal, 2025)

Application of molecular docking in sorption of hydrophobic organic contaminants on black carbon - Tian Liang; Nannan Wan; Yan-Rong Zou; Xuan Kou; Zhao-Wen Zhan; Ping'’an Peng (Science of The Total Environment, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Enhancing the toughness and strength of flame-retardant PLA blends through triglycidyl isocyanurate driven reactive blending - Yao Yan; Chengpeng Zhang; Junjie Guo; Guozhang Gu; Guoxiang Zou; Rong Yang (Chemical Engineering Journal, 2025)

Associations between serum trace elements and biological age acceleration in the Chinese elderly: A community-based study investigating the mediating role of inflammatory markers and the moderating effect of physical activity - Yan Wang; Wenyuan Zhu; Tao Zhang; Qingping Liu; Mengqi Zou; Yujia Xie; Mengruo Wang; Tian Shuai Wang; Yaxian Pang; Tao Jing; Rong Zhang (Journal of Hazardous Materials, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Study on hydrocarbon retention and expulsion of kerogen based on centrifugal swelling method - Tian Liang; Feng Zhu; Zhao-Wen Zhan; Xiao-Hui Lin; Yan-Rong Zou; Ping’an Peng (Organic Geochemistry, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Degradation characteristics and effect mechanisms of estrogens during aerobic composting of chicken manure based on the orthogonal test - Ziwei Liang; Junhao Wu; De-Chun He; Yan Li; Yan-Qiu Liang; Jia-Wu Hu; Meng-Yao Zou; Jian-Feng Ning; Wang-Rong Liu (Journal of Environmental Management, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Study on the swelling of macromolecular geological organic matter with hydrocarbons and heteroatomic compounds - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Shuang Yu; Chang-Chun Pan; Ping’an Peng (Organic Geochemistry, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Determination and petroleum geochemical significance of short-chain alkylbenzenes in lacustrine source rocks - Zhao-Wen Zhan; Guo-Xiang Wang; Yankuan Tian; Xin Zhan; Tian Liang; Yao-Ping Wang; Yan-Rong Zou; Ping'an Peng (Organic Geochemistry, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Insights into the roles of humic acids in facilitating the anaerobic digestion process - Rong Zhu; Miao Yan; Yun Zhang; Hua Zou; Yi Zheng; Rongbo Guo; Shanfei Fu (Waste Management, 2023)

Determination of purines in prepackaged food using optimum acid hydrolysis followed by high performance liquid chromatography - Xiaoyan Feng; Hongkun Ma; Lina Zou; Yingyao Wang; Yannan Zhang; Yan Wang; Jiaxin Chen; Hongzhi Pan; Shengzhong Rong (Food Chemistry, 2023)

A 3D phytic acid cross-linked high-porous conductive hydrogel integrating g-C3N4 for electrochemical multiplex sensing of heavy metal ions - Lu Xiao; Yulan Zhao; Gang Chang; Huiling Yan; Rong Zou; Xiuhua Zhang; Shengfu Wang; Hanping He (Analytica Chimica Acta, 2023)

Elucidating the chemical structures of petroleum resin using solid-state 13C NMR - Tian Liang; Xiao-Hui Lin; Yan-Rong Zou; Zhao-Wen Zhan; Ping'’an Peng (Chemical Geology, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Research on type I kerogen molecular simulation and docking between kerogen and saturated hydrocarbon molecule during oil generation - Tian Liang; Zhao-Wen Zhan; Yan-Rong Zou; Xiao-Hui Lin; Yun Shan; Ping'’an Peng (Chemical Geology, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Origin and genetic family of Huhehu oil in the Hailar Basin, northeast China - Yao-Ping Wang; Fan Zhang; Yan-Rong Zou; Zhao-Wen Zhan; Yulan Cai (Acta Geochimica, 2018)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Analysis of aroma-active compounds in three sweet osmanthus (Osmanthus fragrans) cultivars by GC-olfactometry and GC-MS - Xuan Cai; Rong-zhang Mai; Jing-jing Zou; Hong-yan Zhang; Xiang-ling Zeng; Ri-ru Zheng; Cai-yun Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

A Proteomic Investigation of B Lymphocytes in an Autistic Family: A Pilot Study of Exposure to Natural Rubber Latex (NRL) May Lead to Autism - Chen Shen; Xin-liang Zhao; Weina Ju; Xiao-bing Zou; Li-rong Huo; Wu Yan; Jun-hua Zou; Guo-di Yan; Edmund C. Jenkins; W. Ted Brown; Nanbert Zhong (Journal of Molecular Neuroscience, 2011)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)